EFEKTIFITAS TERAPI AKUPRESUR DALAM MENGATASI NYERI KEPALA LANSIA HIPERTENSI - Marlina, Leni; Yenni, Yenni; Ayuni, Dini Qurrata (Ensiklopedia of Journal, 2024)
Abstract: One of the symptoms of hypertension is headache. If this symptom is not treated, the long-term effect will be the rupture of blood vessels in the brain, causing paralysis and even death. Acupressure is a non-pharmacological therapy that can treat headaches. The aim of the research was to determine the effect of acupressure therapy on headache levels in hypertensive elderly people. Held at the Kemantan Community Health Center. The type of research is Quasy Experiment Design Nonequivalent Control Group. The reseach population was hypertensive elderly who suffered from mild to moderate headache, taken by purposive sampling as many as 12 people in the intervension group and 12 people in the control group. Pain assessment used the Numerical Pain Rating Scale (NPRS) and bivariate analysis used the independent Sample t-test. Statistical tests show that there is an effect of acupressure therapy on the level of headache in hypertensive elderly people. P-value=0,0005 (p value<0,05). It can be concluded that there is an influence of acupressure therapy on the level of headache in hypertensive elderly people. It is hoped that nursing staff at community health centers can improve their ability to carry out acupressure therapy by taking part in training so that they can use this therapy as a nursing implementation to overcome headache symptom eexperiencedby hypertension sufferers.Keywords: Acupressure, Elderly, Headache, Hypertension